Epidemiological trends and clinicopathological features of cutaneous melanoma in sporadic and xeroderma pigmentosum Tunisian patients. (26th October 2016) - Naouali, Chokri; Jones, Meriem; Nabouli, Imen; Jerbi, Manel; Tounsi, Haifa; Ben Rekaya, Mariem; Ben Ahmed, Melika; Bouhaouala, Balkiss; Messaoud, Olfa; Khaled, Aida; Zghal, Mohamed; Abdelhak, Sonia; et al.
Abstract: Background: Epidemiological features and trends of cutaneous melanoma (CM) in North‐African populations remain unclear. Those populations are of particular interest as they belong to a mosaic of various other origins (sub‐Saharan, European Ancestry, and North‐African Berbers). The aim of this study is to draw epidemiological profile and clinicopathological features of CM in the Tunisian population. Methods: Incidence analyses were based on data from regional cancer registries. Clinical data were collected from dermatological departments and xeroderma pigmentosum (XP) referral centers and provided CM clinicopathological characteristics and progression. Statistical analyses were achieved using R packages and SPSS 20.0. Results: The incidence of CM in Tunisia is relatively low (0.5–0.7 per 100, 000 inhabitants per year). Gender differences were observed regarding anatomical distribution ( P = 0.004). Acral lentiginous melanoma (ALM) was the most frequent histological subtype (32.3%); however, nodular melanoma (NM) was the most aggressive and responsible for 54.8% of deaths. CM in XP patients develops at a median age that is 42 years earlier than sporadic cases, with preferential localization on the head and neck ( P < 0.001). Finally, male patients exhibited survival disadvantages compared with females (adjusted hazard ratio (HR) = 2.22, 95% CI: 1.05–4.68, P = 0.037). Conclusions: Cutaneous melanoma features in Tunisia are closer to those of non‐Caucasians, even though gender differences that are similar to those observed in Caucasians were uncovered. This study also emphasizes the aggressiveness of NM and its effect on melanoma patient deaths. Xeroderma pigmentosum stands as the major predisposing host factor.